Global health and the globalization phenomenon: an integrative literature review (Research, Society and Development, 2020)
Global Health is a polysemic expression, but strongly identified as a response to the relatively new problems related to the field of Health, which affect developed and developing countries, as well as underdeveloped countries. Problems such as disease outbreaks that can be prevented by vaccination, health and humanitarian crises, high rates of obesity, unrestricted use of natural resources, among others. In this sense, this article aims to show in the current literature how the field of Global Health is taking shape, linked to contemporary globalization processes. Methodologically, the study took place by means of an integrative literature review, with emphasis on scientific productions published since the 2000s. The main results of the article show that Global Health is a field that involves diplomatic relations between countries, remodeling in the the role of agencies considered hegemonic in the 20th century, such as the World Health Organization (WHO), horizontal proximity between countries in the development of health policies, participation of civil society and second sector actors, recognition of cultural, political and and the need to understand environmental determinants of health. On the other hand, it shows its limits of practical action in contexts marked by neoliberal principles, with minimal state intervention, since the positive results in Global Health depend on the performance of strong national health systems.